Impact of Viloxazine Extended-Release Capsules (Qelbree®) on Executive Function in Adults With ADHD During an Open-Label Extension Study. (April 2023) - Nasser, Azmi; Hull, Joseph; Yarullina, Ilmiya; Qin, Peibing; Rubin, Jonathan
Abstract: Introduction: Executive function deficits (EFDs) are associated with attention-deficit/hyperactivity disorder (ADHD). Viloxazine ER (viloxazine extended-release capsules; Qelbree ® ) is a novel, nonstimulant, FDA-approved treatment for ADHD in persons ≥6 years of age. In a Phase 3, double-blind (DB), placebo-controlled trial in adults (NCT04016779), viloxazine ER-treated subjects exhibited significant improvement in both ADHD core symptoms (inattention and hyperactivity/impulsivity) compared to placebo. In addition, improvement in EFDs was observed in subjects using the Behavior Rating Inventory of Executive Function – Adult Version (BRIEF-A, Self-report), a 75-item scale that assesses aspects of executive function (Metacognition Index [MI]) and problems with self-regulation (Behavioral Regulation Index [BRI]) and overall functioning (Global Executive Composite [GEC]). At Week 6 in DB trial, a statistically significant greater reduction (improvement) was observed in viloxazine ER-treated subjects compared to placebo in the GEC and MI, but not in the BRI. Here, preliminary results of further BRIEF-A assessments in adults during an ongoing open-label extension (OLE) safety trial (NCT04143217) are presented. Methods: Subjects complete the BRIEF-A at baseline and at Week 6 in the DB trial, and at Week 4 and every 8 weeks thereafter in the OLE trial. Subjects rate each BRIEF-A item on a 3-point scale (1=Never, 2=Sometimes, or 3=Often) based on the last month. Raw scores for GEC, MI, and BRI (sum of 70, 40, and 30 items, respectively) were converted to a T-score (mean=50, standard deviation=10; T-score ≥ 65 considered abnormally elevated) and then to a change from (DB) baseline (CFB) T-score. The mean [±SE] CFB T-score was calculated for the GEC, MI, and BRI by study OLE visit, and the mean last on-study OLE visit was analyzed using a paired t-test. Results: In the OLE trial, 157 subjects received viloxazine ER (first subject dosed, 24 Jan 2020; data cut, 30 MAR 2021). The mean [±SE (n)] T-score at DB baseline between placebo and viloxazine ER groups was similar for GEC [70.9 ± 0.82 (177) and 71.0 ± 0.77 (173)], MI [73.6 ± 0.86 (178) and 74.0 ± 0.83 (173)], and BRI [63.9 ± 0.85 (177) and 63.6 ± 0.77 (174)]. The CFB T-score decreased across OLE visits in all three measures. At last on-study OLE visit, the mean [±SE (n)] CFB T-score was significantly improved for the GEC [-12.4 ± 1.23 (121); P<0.0001], the MI (-12.6 ± 1.30 (121); P<0.0001], and the BRI [-10.0 ± 1.04 (122); P<0.0001]; median viloxazine ER dose was 400 mg/day. Conclusions: Following the DB trial, improvement in executive function continued during viloxazine ER treatment in adults throughout the OLE trial, including a significant improvement at subjects' last on-study visit for overall functioning (GEC) and both indices (MI and BRI). Overall, the results suggest adults with ADHD may show improvement in executive function with viloxazine ER treatment. Funding: Supernus Pharmaceuticals, Inc.